FACTORS AFFECTING GROWTH OF SMALL BUSINESS: THE CASE OF A DEVELOPING COUNTRY HAVING EXPERIENCED TRANSITION - Janeska-Iliev, Aleksandra; Debarliev, Stojan (European Scientific Journal, ESJ, 2015)
The purpose of this research is to examine the impact of factors, related to important strategic characteristics, affecting growth of small business, particularly considering a specific economic and cultural context, related to a developing economy and post-socialist country experiencing transition, as is the case of the Republic of Macedonia. For the purposes of this study, 305 questionnaires were collected, selected at random from several lists containing small and medium businesses on the territory of the Republic of Macedonia. Multiple linear regression was used to determine the relationship between the dependent variable, growth and six independent variables, grouped into five constructs: the resources and processes of small businesses, skills and knowledge possessed by the owner and employees of small business, the strategic approach and orientation of small business, the degree of sophistication of the planning activity, and the nature of external environment of small business. Based on the findings presented in this research, empirical support for the proposed model of growth factors of small business has been found. The results strongly confirm three out of six hypothesis. In other words, according to the results, three independent variables: limitations in the internal environment; additional forms of education of the owner; and development of a strategic plan have statistically significant impact on the growth of small business. The theoretical and practical implications of this research refer to identifying and stressing important factors that can stimulate growth of small business in a specific economic and cultural context of developing economy and post-socialist country experiencing transition.